Pengabdian dalam Meningkatkan Mutu Pendidikan Melalui Rumah Belajar dan Konseling Anak - M. Yogi Riyantama Isjoni; Nadia Isni Safitri; Eka Suci Pramana Sari; Arifin Kurniawan; Nurul Fadilla; Thomas Dian Partogi Simbolon; Zhavira Fitri Mardhatillah; Adela Aliana; Denisa Dila Magfiroh; Raja Maulana Aziz; Abby Hendriansyah (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2021)
In the education sector, Kelurahan Maharani has two Islamic Boarding Schools and one Early Childhood Education (PAUD). The learning process in Kelurahan Maharani is carried out online, namely learning at home. Based on observations, there are many parents who complain about online learning. The lack of knowledge and limited time to assist are one of the reasons why parents find it difficult to assist students in learning at home. The learning house service activity was carried out in August which was carried out continuously until the Kukerta period ended. The hope is that with the learning house service activities, it is able to grow and increase the enthusiasm of students in studying at home. In its implementation, the learning house is carried out with small talk, explanations, question and answer and tests. The results obtained are an increase in the understanding of student who participate in home learning activities. This is because there is comfort in the process of learning and learning the basic things of the material to be learned.